HUBUNGAN KELENTUKAN OTOT PUNGGUNG DAN EXPLOSIVE POWER OTOT LENGAN DAN BAHU DENGAN HASIL LEMPAR CAKRAM PADA SISWA PUTRA KELAS VIII MTS NURUL IKHLAS DESA TABING KECAMATAN KOTO KAMPAR HULU KABUPATEN KAMPAR - ', Zulpikar; ', Slamet; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Based on the researcher’s observation of male student in class VIII MTS Nurul Ikhlas Koto Kampar Districk of Kampar. Researcher found discovered a weakness in the prefix and the lack explosive power muscles. Not only that when the disc is removed should the studenr bending so that the desired throw away that is above the average of student that is 12 meter. The purpose of this research is to see how much the corelation of back muscles flexibility with the discus throwing result, exsplosive arm-shoulder muscles with the result of discus throwing and the contribution of flexibility of back muscles and exsplosive power of arm shoulder muscles with the result of discus throwing of male student in class VIII of MTS Nurul Ikhlas Koto Kampar District of Kampar. Population in this research were all students in class VIII of MTS Nurul Ikhlas amount 25 people. Based on population that is not so large and within the limits the researchers set the whole population is used as a sample. The research sample as many as 25 people. Research instrument used were the flexibility of back muscles with bridge up test, explosive power arm-shoulder muscles with two hand medicine ball put test and the result of discus throwing. Data were analyzed by product moment correlation. Based on research results, it can be concluded as follows : 1. There is corelation the flexibility with the result of discus throwing, 2. The corelation of the explosive power arm-shoulder muscles with the result of discus throwing, 3. The corelatin of the explosive power arm-shoulder and the flexibility of back muscles to the result of discus throwing.Key word : flexibility, back muscles, explosive power arm-shoulder muscles , discus throwing.